META ANALYSIS OF THE EFFECT OF THE USE OF MODULE ON STUDENTS' CRITICAL THINKING ABILITY IN PHYSICS AND SCIENCE COURSES - Hasya Syahmi; Yenni Darvina; . Desnita; . Murtiani (Universitas Negeri Padang, 2022)
The twenty-first century is evolving at an incredible rate.. The development of information and communication technology in all aspect of life, including in the learning process has entered the modern era. The ablility to think critically and solve problems skill (problem solving skill) are important skills for surviving in the twenty-first century. The real condition found in the field were that students' critical thinking skills are relatively low during the teaching and learning process. One solution to overcoming this problem is to use learning media namely in the form of modules. Then, it is necessary to have further research on the Module. Meta-analysis is the term for this type of study. Researchers undertake meta-analysis by synthesizing research data, examining, and analyzing research data from a number of previously published studies. Conducting a literature review, gathering data, studying and assessing papers, analyzing and interpreting articles, and producing report results are all steps in meta-analysis. The necessary statistical data must be included in the article, according to the standard. From the data analysis carried out, it can be stated three results of this research. First, the use of the module has a significant effect on the senior high school level compared with an average effect of 0.931 to junior high school level. Second, the use of the module has a significant effect on the Newton’s Gravity material with an average effect of 3.742. Third, the use of the module has a significant effect by using a Contextual Teaching and Learning Model and saintific approach.